2009
DOI: 10.1016/j.gca.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Concordant Rb–Sr, Sm–Nd, and Ar–Ar ages for Northwest Africa 1460: A 346Ma old basaltic shergottite related to “lherzolitic” shergottites

Abstract: Multiple lines of evidence show that the Rb-Sr, Sm-Nd, and Ar-Ar isotopic systems individually give robust crystallization ages for basaltic (or diabasic) shergottite Northwest Africa (NWA) 1460. In contrast to other shergottites, NWA 1460 exhibits minimal evidence of excess 40 Ar, thus allowing an unambiguous determination of its Ar-Ar age. The concordant RbSr, Sm-Nd, and Ar-Ar results for NWA 1460 define its crystallization age to be 346 ± 17 Ma (2r). In combination with petrographic and trace element data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 87 publications
1
42
0
Order By: Relevance
“…This is evident from the comparison of published data for Zagami (cf. this study; Magna et al, 2006;Reynolds et al, 2006;Seitz et al, 2006) that appear to potentially reflect the lithological diversity of Zagami (McCoy et al, 1999), but also because enriched shergottites are probably not representative of the pristine martian mantle as they record contamination by either martian crust or mixing of heterogeneous mantle components (e.g., Herd et al, 2002;Borg and Draper, 2003;Jones, 2003;Warren et al, 2004;Debaille et al, 2007Debaille et al, , 2008Symes et al, 2008;Basu Sarbadhikari et al, 2009;Nyquist et al, 2009;Lapen et al, 2010).…”
Section: Estimating the LI Isotope Composition Of Bulk Marsmentioning
confidence: 77%
See 2 more Smart Citations
“…This is evident from the comparison of published data for Zagami (cf. this study; Magna et al, 2006;Reynolds et al, 2006;Seitz et al, 2006) that appear to potentially reflect the lithological diversity of Zagami (McCoy et al, 1999), but also because enriched shergottites are probably not representative of the pristine martian mantle as they record contamination by either martian crust or mixing of heterogeneous mantle components (e.g., Herd et al, 2002;Borg and Draper, 2003;Jones, 2003;Warren et al, 2004;Debaille et al, 2007Debaille et al, , 2008Symes et al, 2008;Basu Sarbadhikari et al, 2009;Nyquist et al, 2009;Lapen et al, 2010).…”
Section: Estimating the LI Isotope Composition Of Bulk Marsmentioning
confidence: 77%
“…(2) only high-MgO (>15 wt.%) samples are taken into account because they are considered to best reflect the composition of bulk silicate Mars (Nyquist et al, 2009) and because they either reflect primitive melt compositions or are cumulates from high-temperature crystallization of olivine; (3) it is assumed that, at high temperatures, the d 7 Li of the melts directly reflects the d 7 Li value of their martian mantle source with insignificant 7 Li/ 6 Li fractionation by other processes (Tomascak et al, 1999b;Jeffcoate et al, 2007). Using these criteria, new and published data (Table 1) for MgO-rich cold desert/fall meteorites ALH 77005, EETA 79001A, LAR 06319, RBT 04262, Tissint, Y-000097 and Y-980459 are used in the initial estimate, yielding an average d 7 Li of 4.0 ± 1.6& (2r) for the martian mantle.…”
Section: Estimating the LI Isotope Composition Of Bulk Marsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young ages are thus interpreted to represent the last re-equilibration of phosphate with Martian groundwater. Although the interpretation of shergottites as ancient rocks reconciles the age of the Martian surface with that of the current inventory of Martian meteorites, as well as allowing for active convection of the Martian mantle, strong arguments against this concept have been made (Jones, 1986;Borg et al, 2005;Nyquist et al, 2006;Fritz et al, 2007;Gaffney et al, 2007;Jones, 2007). The proposal that shergottites are 4.0 Ga has received considerable attention, because if proven correct, it would have the important implication that the Martian surface is older than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…Bouvier et al (2005Bouvier et al ( , 2007, using Pb-Pb isotopic data from Zagami and a few other shergottites, suggested that these shergottites actually formed 4.0 Gyr ago and that the Sm-Nd and Rb-Sr chronometers of some minerals, particular phosphates, were reset by acidic aqueous solutions percolating through the Martian surface. However, other chronologists have strongly argued for young ages for the shergottites (Nyquist 2006;Nyquist et al 2001Nyquist et al , 2006bMisawa et al 2006;Herd et al 2007;Shih et al 2007;Jones 2007;Bogard and Park 2007b). Experimental studies suggest that pyroxene would be more strongly weathered than plagioclase in aqueous solutions ranging from moderately acidic to moderately basic (McAdam et al 2006).…”
Section: Residue From Thermal Degassing Of An Old Zagamimentioning
confidence: 99%